Improving Junior High School Students' Learning Discipline Through Digital Literacy: A Correlational Study on Science Learning with Dynamic Electricity Material - Darmaji; Astalini; Kurniawan, Dwi Agus; Triani, Elza (LPPM Undiksha, 2025)
In this digital era, digital literacy has become an inseparable skill in the learning process. However, digital literacy is also closely related to students' disciplinary character. This study investigates the relationship between digital literacy and students' disciplinary character in junior high schools, especially in the context of dynamic electricity learning in physics subjects. This study aims to identify how much digital literacy plays a role in developing students' disciplinary character. This research method is a quantitative study with a correlational design. Data were collected using a validated Digital Literacy and Disciplinary Character questionnaire from 100 grade VIII students. Data analysis was carried out using descriptive, normality, linearity, and correlation tests. The study's main results found a significant positive correlation between digital literacy and disciplinary character, with digital literacy explaining 42% of the variation in disciplinary character. This study concludes that higher digital literacy significantly develops students' disciplinary character. These results indicate the importance of integrating digital literacy into the school curriculum to improve technical skills while developing students' disciplinary character. Further research is recommended to explore other factors, such as family environment and school policies, that may influence students' disciplinary character.